1997
DOI: 10.1021/jo9704772
|View full text |Cite
|
Sign up to set email alerts
|

Laser Flash, Laser-Drop, and Lamp Photolysis of 1,3-Dichloro-1,3-diphenylpropane. One- versus Two-Photon Reaction Pathways

Abstract: Low intensity irradiation of 1,3-dichloro-1,3-diphenylpropane (1) in cyclohexane leads to the formation of 3-chloro-1,3-diphenylpropyl radical (2) through homolytic C−Cl bond cleavage. Radical 2 gives rise to final products typical of free radical reactions. Neither 1,2-diphenylcyclopropanes (6) nor 3-cyclohexyl-1,3-diphenylpropene (20) are obtained under these conditions. Nevertheless, high intensity laser irradiation of the initially formed monoradical 2 leads to the 1,3-diphenylpropenyl radical (3) detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…The signal at 360 nm is consistent with the formation of the 1,3-diphenyl-2propenyl radical (9, λ max 360 nm) produced from the 3-chloro-1,3-diphenylpropyl radical (8, λ max 320 nm), according to the mechanism of Scheme 3, which we have already established in the case of cyclohexane as solvent. 10,18 Thus, photolysis of 1 in acetonitrile produced both the propenyl radical 9 and the propenyl cation 3. Clearly, the homolytic cleavage can involve two-photon processes under conditions where the heterolytic cleavage does not; this is consistent with the strong absorption of the benzylic radicals at the laser wavelength, as already noted in the case of nonpolar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…The signal at 360 nm is consistent with the formation of the 1,3-diphenyl-2propenyl radical (9, λ max 360 nm) produced from the 3-chloro-1,3-diphenylpropyl radical (8, λ max 320 nm), according to the mechanism of Scheme 3, which we have already established in the case of cyclohexane as solvent. 10,18 Thus, photolysis of 1 in acetonitrile produced both the propenyl radical 9 and the propenyl cation 3. Clearly, the homolytic cleavage can involve two-photon processes under conditions where the heterolytic cleavage does not; this is consistent with the strong absorption of the benzylic radicals at the laser wavelength, as already noted in the case of nonpolar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…5 Actually, a new spectrum obtained under these conditions showed a higher ratio of radical 2a to the two photon intermediate, 3a (Fig. 1).…”
mentioning
confidence: 85%
“…When irradiating with a 266 nm laser it is useful to place a beam diffuser (which eliminates 'hot' spots in the laser beam) close to the sample in order to get a better observation of monophotonic transients. 5 Actually, a new spectrum obtained under these conditions showed a higher ratio of radical 2a to the two photon intermediate, 3a (Fig. 1).…”
mentioning
confidence: 85%
“…We have previously reported that photolysis of dichlorodiphenylalkanes 1 ( n = 1−3) in cyclohexane produces homolysis of one carbon−halogen bond (Scheme ) . Laser flash photolysis experiments have demonstrated the formation of chloroalkyl radicals 3 , which have the characteristic narrow absorption at 320 nm and are readily quenched by oxygen at close to the diffusion-controlled limit; these are common features of benzylic radicals .…”
mentioning
confidence: 99%